Peran Ganda Istri dalam Memenuhi Kebutuhan Keluarga di Desa Laiba Kecamatan Parigi Kabupaten Muna - Nesti, Nesti; Suyuty, Nasrudin; Alkausar, Muhamad (JURNAL KABANTI: Kerabat Antropologi, 2025)
This study aims (1) to identify and describe the various forms of dual roles undertaken by wives in fulfilling family needs in Laiba Village, Parigi District, Muna Regency, and (2) to explore the factors that influence women to engage in public sector work. This research employs a qualitative approach with data collection techniques including observation, interviews, and documentation. It also draws on the Nature-Culture theory by Sherry Ortner (1996), which discusses the positioning of women within the division of sociocultural roles. The findings indicate that women in Laiba Village perform dual roles: domestic roles such as caring for their husbands, children, and managing household tasks, and public roles such as trading, farming, and working as daily laborers. The primary motivation for these women to work is economic pressure, especially in situations where their husbands' income is insufficient or when the husbands are sick, elderly, divorced, have migrated, or have passed away. Despite facing various challenges, these women continue to carry out both roles in a balanced manner to meet their families’ needs.